Fighter, Worker, and Family Man : German-Jewish Men and Their Gendered Experiences in Nazi Germany, 1933-1941 - Huebel, Sebastian (Book collections on Project MUSE., 2022)
"When the Nazis came to power, they used various strategies to expel German Jews from social, cultural, and economic life. Fighter, Worker, and Family Man focuses on the gendered experiences and discrimination that German-Jewish men faced between 1933 and 1941. Sebastian Huebel argues that Jewish men's gender identities, intersecting with categories of ethnicity, race, class, and age, underwent a profound process of marginalization that destabilized their accustomed ways of performing masculinity. At the same time, in their attempts to sustain their conceptions of masculinity these men maintained agency and developed coping strategies that prevented their full-scale emasculation. Huebel draws on a rich archive of diaries, letters, and autobiographies to interpret the experiences of these men, focusing on their roles as soldiers and protectors, professionals and breadwinners, and parents and husbands. Fighter, Worker, and Family Man sheds light on how the Nazis sought to emasculate Jewish men through propaganda, the law, and violence, and how in turn German-Jewish men were able to defy emasculation and adapt--at least temporarily--to their marginalized status as men."--